Durabilidade natural da madeira de Tetrorchidium rubrivenium em ensaios de campo e de laboratório - Baggio, Priscilla Maia (2014)
The wood over time passes through a process natural what that gradually losing their (mechanical, physical or chemical) properties in a gradual state of decay. This fact is compounded by the action of wood-destroying organisms that under favorable weather conditions such as rain, wind, damage with the quality of the wood. The present study aimed to evaluate the natural durability of wood Tetrorchidium rubrivenium Poeppig & Endlicher (Canemaçu) under the action of deteriorative organisms in field tests and laboratory analyzing two regions of wood, peripheral region and central region. The wood used for this work were obtained from five trees Canemaçu. We analyzed the apparent specific gravity for the two regions studied wood. For the laboratory test was followed to ASTM D 2017 (ASTM , 2005) with modification in the specimens to 2.0 x 2.0 x 0.9 cm , which were sawn parts of the peripheral region and the central region of same samples prepared for testing field with dimensions of 2.0 x 2.0 x 30 . Were analyzed for laboratory testing and field: mass loss and colorimetry and the field test: index behavior, static bending (MOR and MOE) and solubility in sodium hydroxide. For mass density at 12% moisture was obtained for peripheral region 0.483 g / cm ³ and central 0.424 g / cm ³ , which statistically significantly. The loss of mass in the laboratory test for brown rot was similar in the two regions with an average of 33 %, while for white rot results are different, with the peripheral region 23.35% and 36.57 % central region. The colorimetric parameters L *, a * and b * were significantly different depending on the fungal attack of brown rot and white rot in laboratory test values. In field trial samples installed in the open field showed a trend towards higher mass losses for samples of the forest. The deterioration index was reduced with the passage of time of exposure to the environment. The MOE and MOR were being reduced over time, but with periods of oscillation. The values obtained in solubility in 1% sodium hydroxide solution been declining with increasing time of exposure in the field. All wood samples exposed to natural weathering demonstrated a reduction in the b * parameter, causing the browning of the samples. Comparing the results obtained in laboratory tests and field for both regions analyzed the wood, it is concluded that both conditions do not have to be exposed in contact with the ground.